En face slab optical coherence tomography imaging successfully monitors progressive degenerative changes in the innermost layer of the diabetic retina. Issue 1 (31st March 2020) - Katsuyama, Atsuko; Kusuhara, Sentaro; Asahara, Shun-Ichiro; Nakai, Shun-Ichiro; Mori, Sotaro; Matsumiya, Wataru; Miki, Akiko; Kurimoto, Takuji; Imai, Hisanori; Kido, Yoshiaki; Ogawa, Wataru; Nakamura, Makoto
Abstract : Objective: To evaluate the usefulness of en face slab optical coherence tomography (OCT) imaging for monitoring diabetic retinal neurodegeneration with supporting animal experimental data. Research design and methods: We retrospectively examined 72 diabetic eyes over 3 years using Cirrus-HD OCT. Two-dimensional en face slab OCT images of the innermost retina were reconstructed and graded according to the ratio of dark area to total area, and relative red, green, and blue color area ratios were calculated and used as indexes for each en face slab OCT image. Values from en face OCT images were used for statistical analyses. To obtain insight into the pathogenesis of diabetic retinal neurodegeneration, we used the InsPr-Cre;Pdk1 flox/flox diabetic mouse model. Results: Both OCT grade and relative red color area ratio significantly increased with the advancing stage of diabetic retinopathy (p=0.018 and 0.006, respectively). After a mean follow-up period of 4.6 years, the trend was unchanged in the analyses of 42 untreated eyes (p<0.001 and 0.001, respectively). Visual acuity showed a weak but significant negative correlation with the red color ratio on en face slab OCT images, but central retinal thickness did not exhibit a clinically meaningful correlation with values obtained from en face slab OCT images. Immunohistochemical analyses of InsPr-Cre;Pdk1 flox/flox diabetic mice demonstrated the loss of ganglion axon bundles and thinning of laminin without apparent retinal vascular change at the age of 20 weeks. Conclusions: En face slab OCT imaging would be a novel useful modality for the assessment of diabetic retinal neurodegeneration as it could detect subtle optical changes occurring in the innermost retina in diabetic eyes. Our animal experimental data suggest that dark areas observed on en face slab OCT images might be the impairment of the extracellular matrix as well as neurons.